Leadership Factors Motivation Factors and Working Environment Factors that Affect Organizational Engagement of Digital and Information Technology Employees at the Bank for Agriculture and Agricultural Cooperatives - Chinput, Pheeraphat; Seyanont, Arisara (Rajapark Journal, 2025)
This research investigates leadership, motivational, and work environment factors influencing the organizational engagement of digital and information technology employees at the Bank for Agriculture and Agricultural Cooperatives. The primary objective of this quantitative study was to examine how leadership, motivation, and work environment impact organizational engagement. Data were collected through questionnaires administered to employees in the Bank for Agriculture and Agricultural Cooperatives’ digital and information technology department. Descriptive statistics, including frequency, percentage, mean, and standard deviation, were employed for data analysis. Inferential statistics were also utilized for hypothesis testing. The findings indicate that, overall, leadership, motivational, and work environment factors significantly influence the organizational engagement of digital and information technology employees at the Bank for Agriculture and Agricultural Cooperatives.